Pseudomonas aeruginosa Affects Airway Epithelial Response and Barrier Function During Rhinovirus Infection - Endres, Adrian; Hügel, Christian; Boland, Helena; Hogardt, Michael; Schubert, Ralf; Jonigk, Danny; Braubach, Peter; Rohde, Gernot; Bellinghausen, Carla (Frontiers in Cellular and Infection Microbiology, 2022)
Cystic fibrosis (CF) lung disease is aggravated by recurrent and ultimately chronic bacterial infections. One of the key pathogens in adult CF lung disease is P. aeruginosa (PA). In addition to bacteria, respiratory viral infections are suggested to trigger pulmonary exacerbations in CF. To date, little is known on how chronic infections with PA influence susceptibility and response to viral infection. We investigated the interactions between PA, human rhinovirus (HRV) and the airway epithelium in a model of chronic PA infection using differentiated primary bronchial epithelial cells (pBECs) and clinical PA isolates obtained from the respiratory sample of a CF patient. Cells were repeatedly infected with either a mucoid or a non-mucoid PA isolate for 16 days to simulate chronic infection, and subsequently co-infected with HRV. Key cytokines and viral RNA were quantified by cytometric bead array, ELISA and qPCR. Proteolytic degradation of IL-6 was analyzed by Western Blots. Barrier function was assessed by permeability tests and transepithelial electric resistance measurements. Virus infection stimulated the production of inflammatory and antiviral mediators, including interleukin (IL)-6, CXCL-8, tumor necrosis factor (TNF)-α, and type I/III interferons. Co-infection with a non-mucoid PA isolate increased IL-1β protein concentrations (28.88 pg/ml vs. 6.10 pg/ml), but in contrast drastically diminished levels of IL-6 protein (53.17 pg/ml vs. 2301.33 pg/ml) compared to virus infection alone. Conditioned medium obtained from co-infections with a non-mucoid PA isolate and HRV was able to rapidly degrade recombinant IL-6 in a serine protease-dependent manner, whereas medium from individual infections or co-infections with a mucoid isolate had no such effect. After co-infection with HRV and the non-mucoid PA isolate, we detected lower mRNA levels of Forkhead box J1 (FOXJ1) and Cilia Apical Structure Protein (SNTN), markers of epithelial cell differentiation to ciliated cells. Moreover, epithelial permeability was increased and barrier function compromised compared to single infections. These data show that PA infection can influence the response of bronchial epithelial cells to viral infection. Altered innate immune responses and compromised epithelial barrier function may contribute to an aggravated course of viral infection in PA-infected airways.